Kontinuiteta zdravstvene obravnave v patronažnem varstvu po bolnišnični obravnavi otročnice, novorojenčka in ostalih pacientov - Žele, Mojca (Obzornik zdravstvene nege, 2021)
Introduction: Nowadays,community registered nurses are faced with quick discharges from hospital treatment. The continuity of health treatment at home is made more difficult if the documentation concerning the discharge is unsuitable. The aim of the research was to establish the course of continued health treatment in community nursing after hospital treatment of mothers, infants and other patients, and how the discontinuity of health treatment affects the work of community nurses.Methods: A qualitative research method was used. The purposive sample included seven community registered nurses and data was collected using half-structured interviews between December 2018 and January 2019. Data was processed using the method of content analysis.Results: Data description is divided into three thematic parts that define reporting on hospital discharges: (1) Reporting on discharging a patient from hospital treatment, (2) Reporting on discharging an infant and mother from maternity hospital, (3) Discontinuity of health treatment.Discussion and conclusion: The results of the research have shown that a common manner of passing on information should be adopted for continuing community health treatment. It might be sensible to implement a common information system at a national level. The e-Health system could be upgraded to enable community registered nurses' access to health documentation.
Keywords: community nursing; coordination of work; discharge; domače okolje; home setting; koordinacija dela; odpust; patronažna zdravstvena nega